LITERASI DIGITAL DAN PENGARUHNYA DALAM PENCEGAHAN PERILAKU ONLINE BERISIKO PADA SISWA SEKOLAH DASAR USIA REMAJA AWAL DI PROVINSI D.I. YOGYAKARTA - Mustamid, Mustamid; Andriyati, Nofica (STIT AL MULTAZAM, 2022)
In addition to providing convenience and a positive impact on children, the internet also has risks or negative impacts if not used wisely. One of the negative impacts is risky online behavior. The predictor that can predict risky online behavior is digital literacy. This study examines and analyzes the effect of digital literacy (X1) on risky online behavior (Y) of early adolescent students in the Province of D.I. Yogyakarta. This causal correlational study using a cross-sectional survey collected data through an online questionnaire using the Google Form application which was distributed to respondents voluntarily. This research was conducted from June to August 2022 with a total of 304 respondents. The research process includes the preparation of instruments, instrument feasibility tests, data collection through online questionnaires, tabulation, and data analysis. The digital literacy scale is adapted from RodrÃguez-de-Dios, Igartua, GonzÃ¡lez-VÃ¡zquez plus Brian O'Neill Thuy Dinh and Hui Zhang Chang Zhu. Meanwhile, risky online behavior is measured using the Adityar scale. The results showed that digital literacy proved to have a significant effect on the risky online behavior prevention variable. The majority of subjects are in the category of having high/good digital literacy and having low-risk online behavior. However, even though digital literacy tends to be high, coaching and efforts to increase digital literacy for elementary school-aged youth need to be implemented as optimally as possible to further prevent children from being exposed to risky online behavior.